2018
DOI: 10.1111/lit.12163
|View full text |Cite
|
Sign up to set email alerts
|

Promoting NQT linguistic awareness of dialogic teaching practices: a dialogic model of professional development

Abstract: This study offers an insight into the experiences of three newly qualified English primary teachers and their pupils as they sought to develop dialogic teaching in lessons. It draws upon a range of literature from the field of classroom talk, with a particular focus on the work of Robin Alexander to underpin teacher/researcher professional discussion and analysis of periodic video recordings of talk in these classrooms. Supplemented by teacher interviews, the research examines the extent to which a dialogic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Recent research has found that classes with a more conversational approach had higher learning results than classrooms in which teachers speak more (Alexander, 2020;Hennessy & Davies, 2020;Resnick, Asterhan, Clarke, & Schantz, 2018). The more students are participating orally in the classroom discussion the more they are getting better learning outcomes (Bignell, 2019;Reznitskaya & Wilkinson, 2015).…”
Section: Dialogic Teachingmentioning
confidence: 99%
“…Recent research has found that classes with a more conversational approach had higher learning results than classrooms in which teachers speak more (Alexander, 2020;Hennessy & Davies, 2020;Resnick, Asterhan, Clarke, & Schantz, 2018). The more students are participating orally in the classroom discussion the more they are getting better learning outcomes (Bignell, 2019;Reznitskaya & Wilkinson, 2015).…”
Section: Dialogic Teachingmentioning
confidence: 99%
“…The process of development was devoted to the study of the professional discussion and classroom recording performance of the teaching and research staff, and the subsequent interviews with the teachers' teaching experience supplemented the relevant English teaching tools. The study showed that the research on the teaching practices of English teachers through this tool can effectively improve the English teaching level of the teachers [12]. Kim, & Sangki.…”
Section: Introductionmentioning
confidence: 98%
“…While the emphasis is placed on improving students' basic English skills, university English teaching should not only focus on the acquisition and accumulation of students' English language knowledge but, more importantly, improving intercultural communication ability is an important training goal. In this way, college students' practical language application ability can be effectively improved to cross the cultural gap and exchange ideas without barriers in cross-cultural communication [6][7][8][9]. Contemporary college students can organically combine theoretical knowledge learning in the classroom and independent learning on the online platform in the online media environment.…”
Section: Introductionmentioning
confidence: 99%